Characterization of growth and development of sorghum genotypes with differential susceptibility to Striga hermonthica. (19th August 2021) - Kawa, Dorota; Taylor, Tamera; Thiombiano, Benjamin; Musa, Zayan; Vahldick, Hannah E; Walmsley, Aimee; Bucksch, Alexander; Bouwmeester, Harro; Brady, Siobhan M
Abstract : Model sorghum varieties for resistance or susceptiblity to the parasitic weed Striga hermonthica differ in growth, development, root system architecture, hormone abundance, and metabolic gene expression. Abstract: Two sorghum varieties, Shanqui Red (SQR) and SRN39, have distinct levels of susceptibility to the parasitic weed Striga hermonthica, which have been attributed to different strigolactone composition within their root exudates. Root exudates of the Striga-susceptible variety Shanqui Red (SQR) contain primarily 5-deoxystrigol, which has a high efficiency for inducing Striga germination. SRN39 roots primarily exude orobanchol, leading to reduced Striga germination and making this variety resistant to Striga. The structural diversity in exuded strigolactones is determined by a polymorphism in the LOW GERMINATION STIMULANT 1 ( LGS1 ) locus. Yet, the genetic diversity between SQR and SRN39 is broad and has not been addressed in terms of growth and development. Here, we demonstrate additional differences between SQR and SRN39 by phenotypic and molecular characterization. A suite of genes related to metabolism was differentially expressed between SQR and SRN39. Increased levels of gibberellin precursors in SRN39 were accompanied by slower growth rate and developmental delay and we observed an overall increased SRN39 biomass. The slow-down in growth and differences in transcriptome profiles of SRN39 were strongly associated with plant age. Additionally, enhanced lateral root growth was observed in SRN39 and three additional genotypes exuding primarily orobanchol. In summary, we demonstrate that the differences between SQR and SRN39 reach further than the changes in strigolactone profile in the root exudate and translate into alterations in growth and development.